Employment Protection Legislation, Multinational Firms, and Innovation - Griffith, Rachel; Macartney, Gareth (The Review of Economics and Statistics, 2014)
The theoretical effects of labor regulations, such as employment protection legislation (EPL), on innovation is ambiguous. EPL increases job security, and the greater enforceability of job contracts may increase worker investment in innovative activity. But EPL increases firms' adjustment costs, which may lead to underinvestment in activities that are likely to require adjustment, including technologically advanced innovation. In this paper, we find empirical evidence that these effects are at work—in particular, a higher share of multinational enterprise innovative activity in countries with high EPL is technologically advanced.